Integrated Privacy Preserving Data Deduplication Method using Third Party Auditor over Cloud Storage - Antony Xavier Bronson.F, Dr.; Rajagopalan.S, Dr.; Ramamoorthy S, Dr. (International Journal of Engineering and Technology, 2026)
Nowadays the deduplication process plays major role in the field of information technology by handling bigdata and cloud data at the cloud storage. This process occupies less storage because the redundant data are removed and only one copy of the data is kept with high level of trust with security. Traditional method of the handling cloud data is in only one provider, so the same data is available in the provider which causes excessive storage. Existing deduplication algorithms performs the elimination process but it suffers in the performance due to the factors like compression ratio, delay in the process. This problem is overcome by using integrated way of keeping the data with high availability with multi provider interactions through Third Party Auditor (TPA). These interactions are happens through agreement. The privacy level of the data is maintained properly with multi layered structure in order to prevent unauthorized disclosure. The proposed algorithm is compared with various algorithms by considering performance parameters. Analyzes of the deduplication algorithms are carried in efficient manner. The main objective of the proposed method is to integrate more than one cloud provider and maintains only one copy of the data at the cloud storage in highly reliable manner.